Fonctions de production dans l’économie du Québec - Corbo, Vittorio; Dufour, Jean-Marie (L'Actualité économique, 1978)
The purpose of this paper is to study the characteristics of the production process in the Quebec economy. We devote particular attention to two features of the technology: the returns to scale and the substitution possibilities. Two forms of production functions, the Cobb-Douglas and an homothetic translog production function, are estimated for six branches of economic activity. These are: Agriculture; Fishing and Forestry; Mining; Quarying and Oil Wells; Manufacturing; Utilities; Services. Two main conclusions are derived from this work. First, there is strong evidence of constant returns to scale in all branches of the Quebec economy but services. Second, when comparing the Cobb-Douglas model with an homothetic translog model, the hypothesis that the true model is the Cobb-Douglas one cannot be rejected for five of our six sectors. Therefore, there is evidence that the elasticity of substitution is around one. Finally a byproduct of our work has been the construction of capital stock series for the Quebec economy (1960-73) disaggregated into 14 sectors, and two types of capital: construction and machinery and equipment.